2019
DOI: 10.1111/ejn.14584
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase receptor and tissue plasminogen activator as immediate‐early genes in pentylenetetrazole‐induced seizures in the mouse brain

Abstract: Epileptogenesis progressively leads to the rearrangement of normal neuronal networks into more excitable ones and can be viewed as a form of neuroplasticity, the molecular mechanisms of which still remain obscure. Here, we studied pentylenetetrazole seizure-induced regulation of genes for plasminogen activator system in the mouse brain. We found that expression of tissue plasminogen activator (tPA) and urokinase receptor (uPAR) mRNA was strongly increased in the mouse cerebral cortex, hippocampus, striatum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…We had previously shown that Plaur gene expression is induced in various brain structures ( Shmakova et al, 2020 ) in a model of pentylenetetrazole (PTZ)-induced seizures in mice. Here we used miRNA and mRNA isolated from previously obtained brain samples.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We had previously shown that Plaur gene expression is induced in various brain structures ( Shmakova et al, 2020 ) in a model of pentylenetetrazole (PTZ)-induced seizures in mice. Here we used miRNA and mRNA isolated from previously obtained brain samples.…”
Section: Methodsmentioning
confidence: 99%
“…Here we used miRNA and mRNA isolated from previously obtained brain samples. A detailed description of methodology, animal facility and enabling documentation has been previously published ( Shmakova et al, 2020 ). To assess the endogenous level of Plaur-miR1 induction and expression of its target genes, we selected brain regions with the most significant Plaur mRNA induction 3 h after PTZ (Sigma-Aldrich, cat.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations